Pneumothorax, an underappreciated complication with an airway exchange catheter - Rashid, Ali M.; Williams, Charles; Noble, Jason; Rashid, Omar M.; Takabe, Kazuaki; Anand, Rahul J. (Journal of Thoracic Disease; Vol 4, No 6 (December 21, 2012): Journal of Thoracic Disease, 2012)
While airway exchange catheters (AEC) are designed to safely maintain a secure airway and sometimes allow for ventilation while exchanging an endotracheal tube or performing a trial tracheal extubation, their use is sometimes associated with devastating complications. Pneumothorax is an underappreciated complication with AECs that can occur even in the absence of high pressure ventilation with quick clinical deterioration. The development of a pneumothorax can be difficult to distinguish from other potential causes of clinical deterioration and the clinician should maintain a high level of suspicion for quick diagnosis and treatment. Here we report a case of tension pneumothorax leading to cardiovascular collapse that occurred very suddenly with the introduction of an AEC. This pneumothorax presented in an atypical manner by all monitors available except for blood pressure monitoring. Therefore this case highlights the need for strong clinical suspicion of pneumothorax with the use of AECs.